THE IMPACT OF RELIGIOUS BELIEFS AMONG ACEHNESE EFL PRE-SERVICE TEACHERS - Rahmi Rahmi (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
It is well known that the belief systems of teachers have a considerable impact on teaching. In the end, teachers' beliefs—which also affect their consciousness, teaching attitude, teaching methods, and teaching policies—have an impact on students' development (Shinde & Karekatti, 2012). Although there has been extensive research on teachers' beliefs, there has not been much done explicitly on teachers' or pre-service teachers' religious beliefs. Therefore, this study sought to understand the significance of religious beliefs in Aceh's EFL pre-service teachers' lives. Five pre-service teachers from an English Language Education Department at one of the Islamic universities in Aceh provided the data in the form of reflective journals and interviews. Using codes and themes, the collected data underwent a qualitative analysis. The results showed that religion had an impact on pre-service teachers in five areas, including going through a tough period, participating in religious activities, interacting with others, seeking knowledge, and considering their future careers.